Examining the Effectiveness of the "Storigami in Child Development" Course - Bafrali, Gorsev; Tanju Aslışen, Ebru Hasibe (Asian Journal of Early Childhood and Elementary Education, 2025)
This study is a qualitative research examining the perspectives of undergraduate students who are majoring at Child Development enrolled in the course "Storigami in Child Development." at a university. To analyze changes in students’ perceptions of the Storigami technique, open-ended questions were asked at the beginning and end of the semester. Additionally, their opinions on the course were assessed through reflective writings throughout the semester. This study represents the second phase of a curriculum development initiative designed to integrate the highly effective Storigami technique into Child Development programs as a course. In this regard, it aims to investigate the effectiveness of the implemented curriculum. The results indicate a positive improvement in students’ perceptions throughout the course. They reported improvements in their storytelling, creativity, and paper-folding skills. Additionally, their knowledge became more informed and extended thanks to the course content. Beyond its contribution to the literature, this study provides various recommendations for Child Development students, preschool teachers, and teacher candidates.